á¸¤IKMAH DALAM PERSFEKTIF ALQURAN - Tahir, Muhyiddin (Institut Agama Islam Negeri (IAIN) Palu, 2012)
Abstract: The Qurâan is admitted by Muslims as a collection of Gods words which have been recorded in the form of a book. The word á¸¥ikmah is one of the words repeatedly stated in the Qurâan, but the word will have its own meaning, when coupled with specific words in the Qurâan. Therefore, the use of the word in the Quran should be interpreted and understood. That understanding can be extracted from the Quran itself, which is also considered the á¸¥ikmah because it is full of wisdom that should be applied, both in individual life and in the social life.Kata Kunci: hikmah, Alquran, mawÄâiáº, kenabian